Widespread infection of Areospora rohanae in southern king crab (Lithodes santolla) populations across south Chilean Patagonia - Rodriguez, S. M.; Uribe Paredes, Juan Carlos; Estay, S. A.; Palacios, M.; Pinochet, R.; Oyarzun Godoy, Sylvia; Valdivia, N. (My University, 2019)
Cottage cheese disease is caused by microsporidian parasites that infect a wide range of animal populations. Despite its potential to affect economically important activities, the spatial patterns of prevalence of this disease are still not well understood. Here, we analyse the occurrence of the microsporidian Areospora rohanae in populations of the king crab Lithodes santolla over ca 800 km of the southeastern Pacific shore. In winter 2011, conical pots were deployed between 50 and 200 m depth to capture crabs of a wide range of sizes. The infection was widely distributed along the region, with a mean prevalence of 16%, and no significant association between prevalence and geographical location was detected. Males, females and ovigerous females showed similar prevalence values of 16.5 (13-18.9), 15 (9.2-15) and 16.7% (10-19%), respectively. These patterns of prevalence were consistent across crab body sizes, despite the ontogenetic and sex-dependent variations in feeding behaviour and bathymetric migrations previously reported for king crabs. This study provided the first report of the geographical distribution of A. rohanae infecting southern king crabs.
Keywords: microsporidia; lithodidae; crab fishery; pathogens; magellan region